2003
DOI: 10.5551/jat.10.13
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Carotid Atherosclerosis Patterns Detected by Ultrasonography in Japanese Elderly Patients with Aortic Aneurysm

Abstract: To clarify current changes in the patterns of carotid atherosclerosis in Japan, carotid ultrasonographic findings in Japanese male patients with aortic aneurysm were compared between two groups examined in different periods. The first group was recruited from 42 consecutively examined patients in 1997, while the second group consisted of 40 consecutive patients from September, 2001 to January, 2002. Carotid lesions were analyzed by computer, and classified into three types based on the texture: echolucent, hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Abdominal vascular ultrasound can be ordered to evaluate the possibility of abdominal aorta aneurysm, and particularly the presence of thrombus [ 19 ]. This condition is more common in elderly men than in women (ratio of 7:1) and is usually diagnosed by physical examination of the abdomen and ultrasound [ 19 , 30 ]. The specific investigation of abdominal aorta aneurysm, could potentially explain the difference in utilisation of abdominal vascular ultrasound between men and women in the older population.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal vascular ultrasound can be ordered to evaluate the possibility of abdominal aorta aneurysm, and particularly the presence of thrombus [ 19 ]. This condition is more common in elderly men than in women (ratio of 7:1) and is usually diagnosed by physical examination of the abdomen and ultrasound [ 19 , 30 ]. The specific investigation of abdominal aorta aneurysm, could potentially explain the difference in utilisation of abdominal vascular ultrasound between men and women in the older population.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly patients with risk factors for vascular disease are required to have an adequate screening through their primary care. Iwamoto et al 47 indicated that hypoechoic lesions of the aorta detected by ultrasonography, which are considered to be a rapid screener for vascular lipid deposition, hemorrhage, or loose fibrous tissue, and severe stenosis have higher possibilities of becoming an aorta aneurysm rather than hyperechoic lesions. The sonographer should search for focal dilatation of the abdominal aorta or lack of normal distal tapering.…”
Section: Abdominal Aorta Aneurysmmentioning
confidence: 98%
“…Localized, thickened IMT of 2.1 mm or more in thickness (plaque) and stenotic lesions occupying more than 70% of the lumen diameter were assessed as carotid lesions (14).…”
Section: Carotid Ultrasonographymentioning
confidence: 99%